Getting to know the truth and ability to predict in natural sciences - Grochowska, Irena (Studia Ecologiae et Bioethicae, 2008)
Representatives of natural sciences (biologists, physicists, chemists) are scientists who deal with the part of knowledge regarding aspects of natural reality. If we regard natural reality to cosmos we can say that the possibilities of direct research are possible only in a small area. In spite of the limitations of access researchers do not get lost in the chaos of already studied separate images, but the gained experience, together with evolution of human thought create more and more uniform image, despite of numerous missing pieces. Natural reality is complex, complicated and difficult to familiarize. One of the main problems of studying the natural reality is its complexity and variety of dynamic processes which create this reality. Another difficulty is the systematized and uniform terminology and concepts used. In the days of fast developing new disciplines and atomization of science it is almost impossible. Natural reality exists independent of our knowledge of it. However the awareness of the difficulties and limitations in studying it should help in being responsible for the process of acquiring knowledge. Acquiring knowledge should therefore mirror the mechanisms existing in nature, that is why it was necessary to discuss the dynamics of getting to know nature with indication to some definitions of truth and its kinds, as well as various research mistakes. Next to getting to know the things themselves it is important in science to detect and eliminate the mistakes. It is necessary to know the criteria of acknowledging or denying the genuine and false nature of research results, hypothesis or new theories in order to properly acquire knowledge about the natural world and properly communicate the results of studying.